111 Arrhythmogenic right ventricular cardiomyopathy-like phenotype revealed by endurance training in heterozygeous desmoglein2 mutants. (16th May 2012) - Fabritz, L; Fortmueller, L; Kucerova, D; Sakhtivel, S; Syeda, F; Kirchhof, P; Leube, R E; Krusche, C
Abstract : Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a rare cardiomyopathy but significantly contributes to sudden cardiac death in young otherwise healthy patients, especially long durance athletes. 5%–10% of patients with ARVC harbour mutations in the extracellular domains of the desmoglein (DSG) 2 gene. To assess the role of DSG2 in the ARVC pathomechanism, mice lacking exons 4–6 of the endogenous DSG2 gene (DSG2mt) were generated. Homozygous DSG2mt/mt mice developed dilatation of ventricles and pronounced fibrosis. Heterozygous DSG2mt/wt mutants, however, did not show such morphological alterations. Objective: To study whether physical exercise provokes a cardiac phenotype in DSG2wt/mt mice they were subjected to endurance training together with wild-type (WT) littermates. Methods/Results: Group swimming training sessions were performed 6 times a week starting with 5 min and gradually incrementing to 90 min/d for 7 weeks. Echocardiography was performed before and after training using a small animal ultrasound unit. Right ventricular (RV) diameters were increased in DSG2wt/mt both compared to pretraining and compared to WT after training. Right ventricular function was also decreased after training compared to pretraining and compared to WT littermates (see Abstract 111 table 1 for values, *p<0.05, d = diastolic, s = systolic, lav = long, sav = short axis view, FAC = fractional area shortening, HR = heart rate). Neither left ventricular diameters nor function differed between DSG2wt/mt and WT littermates. Electrophysiological studies in Isolated Langendorff DSG2wt/mt and WT hearts showed comparable ventricular action potential duration and effective refractory periods. DSG2 mutation correlated with increased arrhythmia inducibility after endurance training. Ventricular arrhythmias were induced in 5 of 8 DSG2wt/mt, but in none of 7 WT hearts during right ventricular stimulation by a single extrastimulus (p=0.03). In conclusion, endurance training reveals an ARVC-like phenotype in otherwise healthy and morphologically inconspicuous DSG2wt/mt mice presenting right ventricular dilatation, decreased right ventricular contractility and increased inducibility of ventricular arrhythmias during right ventricular pacing.